Translation and cultural adaptation of a prostate cancer screening decision aid: a qualitative study in Portugal - Bruno Heleno; Sofia Baptista; Marta Pinto; Andreia Teixeira; Kathryn L Taylor; Carlos Martins; Bruna Guimarães; Diogo China; João Pedro Ramos (BMJ Open)
Objectives To translate and culturally adapt an English language patient decision aid addressing prostate cancer screening, so it can be used by Portuguese men.Design Qualitative study. We followed the European Centre for Disease Prevention and Control’s (ECDC) five-step, stakeholder-based approach to adapting health communication materials: (1) selection of materials and process coordinators, (2) early review, (3) translation and back translation, (4) comprehension testing with cognitive semi-structured interviews and (5) proofreading. Content analysis was performed using Ligre software.Setting and participants Cognitive interviews with 15 men to refine a decision aid after its translation. Eligible participants were Portuguese native-speaking men aged 55–69 years old recruited from the local community (urban and suburban) of Oporto district through advertisements in social media and senior universities between January and March 2019. A previous diagnosis of prostate cancer was the single exclusion criterion.Results Five main themes are presented: informational content, information comprehension, sociocultural appropriateness, feelings and main message and personal perspective concerning prostate cancer screening. Most men found the translated version of the decision aid to be clear, comprehensive and appropriate for its target population, although some suggested that medical terms could be a barrier. The data collected from men’s interviews afforded the researchers the opportunity to clarify concepts and expand existing content.Conclusions A decision aid was successfully translated and adapted to the Portuguese cultural setting. Our ECDC based approach can be replicated by other workgroups to translate and culturally adapt decision aids.